Effects of seasonal inundation on methane fluxes from forested freshwater wetlands. (23rd July 2021) - Hondula, Kelly L; Jones, C Nathan; Palmer, Margaret A
Abstract: Methane emissions from small freshwater ecosystems represent one of the largest components of uncertainty in the global methane budget. While these systems are known to produce large amounts of methane relative to their size, quantifying the timing, magnitude, and spatial extent of their emissions remains challenging. We begin to address this challenge in seasonally inundated forested mineral soil wetlands by (1) measuring wetland methane fluxes and hydrologic regime across both inundated and non-inundated soils, (2) characterizing how wetland hydrologic regime impacts the spatial extent of methane emission source areas, and (3) modeling average daily wetland-scale flux rates using four different upscaling techniques. Our results show that inundation extent and duration, but not frequency or depth, were major drivers of wetland methane emissions. Moreover, we found that methane fluxes were best described by the direction of water level change (i.e. rising or falling), where emissions were generally higher when water levels were falling. Once soils were inundated, subsequent changes in water level did not explain observed variability of methane concentrations in standing water. Finally, our spatial modeling suggests that representing inundation and associated methane source areas is a critical step in estimating local to regional scale methane emissions. Intermittently inundated soils alternated between being sources and sinks of methane depending on water level, soil moisture, and the direction of water level change. These results demonstrate that quantifying the hydrologic regime of seasonally inundated forested freshwater wetlands enables a more accurate estimation of methane emissions.